Analysis Model of the Impact of the Covid-19 Pandemic on the Profitability of SMEs - Ardian Widiarto; Lardin Korawijayanti; Arum Febriyanti Ciptaningtias; Tutik Dwi Karyanti (Yayasan Ilomata, 2022)
This study aims to and analyze the extent of the influence of the covid-19 pandemic on the Profitability of the Water Hyacinth Craft Cluster SMEs